Three-phase Electric Motor Control with a Manual Forward Reverse Control System Equipped with a Delay Timer - Arnold. R. Rondonuwu; Julianus. G. Daud; Eliezer. M Rongre; Amelia Rorong; Josua Supit; Ricky. F. Mare; Aldy Werung; Aril Najoan; Willgy Kirojan (Ravine Publisher, 2025)
The control of three-phase electric motors with manual forward and reverse control systems equipped with off-timers (TOF) is a production solution with a simple structure and relatively low cost compared to other systems. Three-phase induction motors typically work via electromagnetic induction from the stator winding to the rotor, making them the preferred choice in both large and small industries due to their accommotivity and efficiency. The purpose of this study was to determine and analyze the control of a three-phase electric motor with a manual back and forth control system equipped with a delay timer. The research method used is secondary data analysis from various relevant and valid sources. The results showed that the manual back and forth control system with TOF is very effective in moving production equipment efficiently and reliably. The implications of this study show that with current technological developments, the use of three-phase electric motors with manual back and forth control systems equipped with TOF has become very important in improving operational efficiency and effectiveness in the industrial world.